From nationally bounded to pan-European inequalities? On the importance of foreign countries as reference groups - Jan Delhey; Ulrich Kohler (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2005)
In sociology, the appropriateness of national approaches for understanding social inequality in today's societies is being increasingly questioned, and EU-wide approaches are advocated instead. In this paper, we link the growing debate about national or EU-wide approaches to reference group theory, investigating whether comparisons with foreign countries influence levels of individual life satisfaction. Our results indicate that, on the one hand, more people can be assumed to have a national frame of reference than a broader international one; on the other hand, among those who do have an idea of how average people in other countries live, cross-border comparisons certainly influence people's satisfaction with life. Upward comparisons in particular are important: The more people feel personally deprived, relative to other countries, the less satisfied they are with their lives. In contrast, the feeling of relative gratification has a much smaller impact on life satisfaction, and often no impact at all. This leads us to conclude that EU-wide approaches to inequality do make sense, but that there is also no need to jettison national approaches completely.
Keywords: 300; Vergleich; International; EU-Staaten; Soziale Ungleichheit; Meinung; Lebenszufriedenheit